Competing by Design : the Power of Organizational Architecture. - Nadler, David (Oxford University Press, USA, 1997)
If the defining goal of modern-day business can be isolated to just one item, it would be the search for competitive advantage. And, as everyone in business knows, it's a lot harder than it used to be. On the one hand, competition is more intense than ever--technological innovation, consumer expectations, government deregulation, all combine to create more opportunities for new competitors to change the basic rules of the game. On the other hand, most of the old reliable sources of competitive advantage are drying up: the hallowed strategies employed by GM, IBM, and AT & T to maintain their seem.